Bridging Healthcare Horizons: Illuminating Pakistani Medical Students' Perspectives on Telemedicine - Said, Sadaf; Khan, Adeel; Talreja, Commando; Nazir, Nosheen; Ibrahim, Hossam Farag; Iqbal, Shazia; Hamza, Ali; Samra, Latif; Najaf, Najaf; Gul, Tehleel; Hayder, Zeeshan; Murtaza, Ghulam (International Journal of Health, Medicine and Nursing Practice, 2024)
Purpose: In the evolving landscape of global healthcare, telemedicine stands out as a beacon of progress, offering enhanced accessibility. Nowhere is its impact more critical than in the rural expanse of Pakistan, where traditional healthcare struggles to reach. This research delves into the minds of Pakistani medical students, a cohort pivotal in steering the future of healthcare delivery in the country. Methodology: The research design for your study can be described as cross-sectional or survey research, focusing on understanding the telemedicine exposure, interest levels, and plans for future utilization among Pakistani medical students across 20 medical schools. Target Population: The target population in your study comprises Pakistani medical students enrolled in the 20 medical schools included in the study. Findings: Among the 396 students surveyed, 24% boasted prior exposure to telemedicine, while a noteworthy 52% expressed unwavering intentions to incorporate it into their future medical practices. Notably, 73.8% of those with prior exposure were resolute in their commitment to using telemedicine, compared to 43% without prior exposure. Among the undecided students, 21% had been exposed previously, shedding light on the profound influence of exposure on shaping future intentions. Unique Contribution to Theory, Policy, and Practice: This research goes beyond the surface exploration of medical students' attitudes towards telemedicine; it makes a distinctive contribution to theoretical frameworks, policy development, and practical implications. The study acts as a theoretical cornerstone by shedding light on the intricacies of the awareness gap within this demographic. From a policy perspective, the findings provide policymakers in Pakistan with a nuanced understanding of the current state and future potential of telemedicine integration into the healthcare system. The practical implications are profound, emphasizing the urgent need for early education in telemedicine to prepare the next generation of healthcare professionals for the challenges and opportunities presented by an evolving healthcare landscape.